Rola wileńskiego typografa Józefa Zawadzkiego w rozwoju czasopiśmiennictwa polskiego na Litwie w epoce porozbiorowej - Kowal, Jolanta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
Józef Zawadzki, the Vilnius bookseller and the editor, the animator of many important publishing undertakings, contributed extremely effectively to sustaining and the development of the scientific‑literary movement in Lithuania in the partition age. Moreover, he became involved very actively in coming into existence and publishing periodicals. He spared no effort to publish “Vilnius Daily” (in both periods of appearing it) or “Vilnius Literary Newspaper”. All action taken in this direction resulted from Zawadzki’s belief that magazines would influence the cultural life of the country very positively and be a place of the constructive criticism, as well as publishing and book advertisements. He cared about it both as the experienced editor, for whom the evaluation of published work was extremely helpful in gradual developing publishing successive initiatives, and for the bookseller caring for the information about the available writing production so that it could get through to the widest circle of recipients and arouse their interest.